Diagnozowanie ubóstwa ekonomicznego na przykładzie Regionu Pomorskiego - Plecka, Małgorzata (Annales. Etyka w Życiu Gospodarczym, 2008)
The main goal of this paper is a collation of methods for diagnosing subjective poverty. The comparison concerns the methods of identification of poverty in the sub-regions of the Pomeranian region. The methods of identification proposed by the author indicate that the proposed methods identify poverty much more precisely than the universal methods. It can be considered to carry on the policy of limiting poverty areas based on the local monitoring. The assembled conclusions can allow improvement of accuracy of directing social help and at the same time can increase acceptance of the rules used in administering this help.